Study of mechanical properties of prototype optical phase conductor for tropical climate conditions in Indonesia - Syamsudin Rahardjo; Solechan -; Rubijanto JP (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. To access the electrical and telecommunications networks required huge costs because there is no infrastructure. To overcome this problem the government is targeting the national electrical capacity 57 thousand Megawatts in 2016 by appointing the State Electricity Company. Target national of Java-Bali distribution network throughout 27.779 km. PLN uses electricity transmission line from the plant to the substation through the tower-tower SUTT and SUTET. This study makes OPPC cable used for extra high voltage power conductors and internet network data that has reliable performance and durable. These goals will be achieved when the known characteristics andmechanical properties OPPC cable. Making cables OPPC by varying the amount of reinforcing steel galvanized wire andtwisting torsional stress magnitude for analyzing mechanical properties ranging impact strength and tensile. The mechanical properties of artificial OPPC cable when compared with mechanical properties that are owned by the ACSR cable and commercial OPPC should be equal or close to its value before the applied field. The results of material testing OPPC cable diameter of 3 cm for Type-voltage torsional twisting 36/6/24 RBS 50% have the impact strength and tensile highest of 112.27 kN and 61.26 MPa. While the impact strength and tensile cables that OPPC least 3 cm in diameter with a voltage selection of the type of 36/6/24 RBS 25% of 63.24 kN and 36.36 MPa. The tensile strength and impact influenced the amount of galvanized steel wire and twisting torsional stress. The more galvanized steel wire and high torsional twisting voltage, proportional to the impact strength and tensile increased.